2019
DOI: 10.1002/jimd.12130
|View full text |Cite
|
Sign up to set email alerts
|

The diagnosis of inborn errors of metabolism by an integrative “multi‐omics” approach: A perspective encompassing genomics, transcriptomics, and proteomics

Abstract: Given the rapidly decreasing cost and increasing speed and accessibility of massively parallel technologies, the integration of comprehensive genomic, transcriptomic, and proteomic data into a “multi‐omics” diagnostic pipeline is within reach. Even though genomic analysis has the capability to reveal all possible perturbations in our genetic code, analysis typically reaches a diagnosis in just 35% of cases, with a diagnostic gap arising due to limitations in prioritization and interpretation of detected varian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 88 publications
(169 reference statements)
0
56
0
Order By: Relevance
“…Organic aciduria can be found in both children and adults that shows various symptoms as tremors, sleepiness, headaches, feeling tired, and seizures (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). In line with existing evidence on the potential use of 2-hydroxyglutaric acid, 2-methylglutaric acid, the authors report on a novel methods and processes to detect these urine metabolites as a source of biomarkers for metabolic disorders.…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…Organic aciduria can be found in both children and adults that shows various symptoms as tremors, sleepiness, headaches, feeling tired, and seizures (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). In line with existing evidence on the potential use of 2-hydroxyglutaric acid, 2-methylglutaric acid, the authors report on a novel methods and processes to detect these urine metabolites as a source of biomarkers for metabolic disorders.…”
Section: Discussionmentioning
confidence: 82%
“…In human metabolome database, 2-methylglutaric acid is known as a derivative of leucine metabolite (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). It is suggested that secretion of methylglutaric acid can be found in the urine of patients showing lack of 3-methylglutaconyl coenzyme A hydratase and 3-hydroxy-3methylglutaryl-CoA lyase deficiency during a type of inborn error of metabolisms.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations